2022
DOI: 10.1108/jhti-01-2022-0038
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumers’ preferences for green hotels – the roles of perceived green benefits and environmental knowledge

Abstract: PurposeThis study aims to examine the influence of environmental knowledge on perceived green benefits and green hotel patronage intention. It also aims to investigate the influence of perceived green benefits on attitude towards green hotel stay and patronage intention.Design/methodology/approachThe purposive sampling method was used in this study. A total of 262 respondents completed the survey questionnaire. For data testing, the partial least squares approach was used.FindingsEnvironmental knowledge positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 86 publications
(132 reference statements)
1
4
0
Order By: Relevance
“…Among China's Generation Z, functional value has the most significant influence on the willingness to stay in green hotels. This is consistent with the views earlier proposed by Tan (2023) [ 64 ] and other scholars, who believed that among perceived green advantages, functional benefits have the most significant impact on the willingness to stay in green hotels. The emphasis on functional value implies that China's Generation Z places more importance on the practical facilities and actual prices of eco-hotels.…”
Section: Discussionsupporting
confidence: 92%
“…Among China's Generation Z, functional value has the most significant influence on the willingness to stay in green hotels. This is consistent with the views earlier proposed by Tan (2023) [ 64 ] and other scholars, who believed that among perceived green advantages, functional benefits have the most significant impact on the willingness to stay in green hotels. The emphasis on functional value implies that China's Generation Z places more importance on the practical facilities and actual prices of eco-hotels.…”
Section: Discussionsupporting
confidence: 92%
“…There are also criticisms of the true purpose of a firm's CSR initiatives and that consumers may perceive the firm's products to be of low value (Du et al , 2011; Lin and Chang, 2012). Consumers tend to have higher purchase intention for a firm's products or brands when associated with CSR (Brown and Dacin, 1997; Creyer and Ross, 1997; Dean, 2004; Sen and Bhattacharya, 2001; Sen et al , 2006), which shows a positive association between firm social performance and financial performance (Garay and Font, 2012; Luo and Bhattacharya, 2006; McGuire et al , 1988; Nicolau, 2008; Stanwick and Stanwick, 1998; Tan, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Consumers perceived green benefits result from the effective awareness that green products can reduce environmental damages and promote environmental protection (Ogiemwonyi et al, 2023;Yue et al, 2021), are better for health, and have superior quality and taste (Silva et al, 2021). While recent literature, Tan (2022), found that environmental knowledge positively influences all GPB, other research shows that consumers who perceive benefits in green products tend to have greater EC and pro-environmental behaviors (Pickett-Baker & Ozaki, 2008). Since it is expected that young consumers formulate more positive beliefs about green products, recognizing their perceived benefits, we formulate the following hypotheses:…”
Section: Green Perceived Benefitsmentioning
confidence: 99%